Discriminating between essential thrombocythemia and masked polycythemia vera in JAK2 mutated patients. Issue 6 (3rd March 2014) - Barbui, Tiziano; Thiele, Jürgen; Carobbio, Alessandra; Guglielmelli, Paola; Rambaldi, Alessandro; Vannucchi, Alessandro M.; Tefferi, Ayalew
<x xml:space="preserve">Abstract</x> In patients not meeting the required hematocrit (HCT) or hemoglobin (Hb) thresholds according to BCSH and the WHO diagnostic criteria, the diagnosis of masked polycythemia vera (mPV) has been proposed. A comparison of HCT or Hb values with the expression of JAK2V617F, JAK2 exon 12, and CALR mutations in strictly WHO‐defined 257 overt PV and 140 mPV (59 mPV according to BCSH) and 397 patients with essential thrombocythemia (ET) was performed. Hb and HCT thresholds of mPV patients were significantly higher than JAK2V617F ET (P < 0.0001). The best cut‐off for Hb to discriminate JAK2‐mutated ET from PV was 16.5 g/dL for males and 16.0 g/dL for females. For HCT, this was 49% in males and 48% in females. The proportion of patients correctly classified as ET or PV when regarding Hb or HCT levels was 95% in males and 93% in females and 94% in both males and females, respectively. Am. J. Hematol. 89:588–590, 2014. © 2014 Wiley Periodicals, Inc.